Effect of Distance Learning Challenges during Covid19 Pandemic to Teachers’ Self Care - Comia, Eva L. (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
Positive feelings encourage higher participation in teaching. This study examined the respondents’ emotional self- care during the COVID-19 pandemic. The researcher explored the effect of distance- learning challenges during COVID-19 pandemic to the emotional self-care of the teachers. Descriptive correlational research design was used in the study with a questionnaire as the main tool in gathering the needed data among one-hundred seventy one (171) respondents identified using complete enumeration among elementary school teachers in the Division of Quezon City, Philippines. The data gathered were treated and analyzed using mean, weighted mean, chi – square and Pearson r. The mean age of the respondents is 40.43, female dominated at 73 percent. Most of respondents were teaching in the primary level that teaches general content courses. About 20 percent of the respondents had been in the field for about 11 – 15 years. Civil status and challenges, civil status and grade level taught to emotional self – care, grade level taught to teaching performance, challenges to self – care, challenges to teaching performance, and self-care to teaching performance revealed a significant relationship. Findings of the study is deemed contributory to possible adjustments to faculty development plan to adapt to changing roles from physical to virtual set – up.